Maternal Factors Associated with Stunting in Children under Five in Asia: A Systematic Review - I Gede Arya Satya Darma; I.P. Adi Wibowo; Komang Hendra Setiawan; Made Suadnyani Pasek (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2026)
Introduction: Multiple maternal factors influencing pregnancy, fetal development, and early childhood care collectively contribute to stunting, a major health concern among children under five across Asia. Variations in maternal nutritional status, reproductive health, hygienic practices, and access to health services underscore the need to identify the most consistent risk factors. Method: PubMed, ScienceDirect, and Google Scholar were utilized to identify relevant literature. The inclusion criteria encompassed quantitative studies examining maternal factors associated with stunting among children under five in Asian countries. Eligible articles were those published between 2019 and 2024 and available in full text in English. Study selection followed the PRISMA flowchart, and quality assessment used the JBI Critical Appraisal Checklist. Discussion: A total fifteen studies were included and most studies used a cross-sectional design. Analysis identified twenty terms maternal determinants of stunting, including maternal age, educational level, nutritional, and employment status. Several behavioral factors such as handwashing practices, exposure to cigarette smoke, antenatal care compliance, and maternal disease history were also reported as significant although only in a limited number of studies. These factors influence stunting through biological, social, economic, and environmental pathways that affect child growth from pregnancy through early life. Conclusion: Maternal factors have an important role in stunting among children in Asia. The most consistent determinants are maternal age, maternal education, and maternal nutritional status. Strengthening nutrition programs, improving maternal health education, and enhancing access to maternal care services are essential to reduce stunting.